The Governance of Educational Welfare Markets: A Comparative Analysis of the European Social Fund in Five Countries - Stănuș, Cristina; Pop, Daniel (Peter Lang International Academic Publishers, 2015)
This book is a first exploratory inquiry into possible educational selectivity effects of the European Social Fund (ESF). It assesses the extent of the gap between the social policy objectives set through regulatory competences in multi-level governance and the structure of incentives it breeds in practice, with a broad range of implications for the capacity of the government to control for an equitable distribution of services at the community level. The chapters emphasize the educational selectivity involved in national policy decisions concerning ESF implementation in the five countries, the role of informal mechanisms in fine-tuning implementation, the negative effects of formalization and failures in accommodating the complexity of goals which characterizes the ESF, as well as the overall fairness of ESF implementation towards the most disadvantaged groups in society. The empirical analysis suggests that social-service delivery contracting as an instrument of governance is no longer regulating against risks for beneficiaries, but fuels increased social division in access to public services.